1998
DOI: 10.1017/s026030550001452x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the densification of polar firn: characterization of the snow–firn transition

Abstract: T he tra nsform ation of dry snow to firn is described by th e tra nsiti on b etween d en sification by d eformationless res tacking a nd d ensificati on by p ower-l aw creep. The obse rved decrease with temperature of the dens it y at the snow-firn transiti on seem s to res ult from th e competition betwee n g rain-bo und a r y sliding a nd power-l aw creep. Th ese two densification processess occ ur concurrenLl y in snow, a lthoug h there a re probably micro-regions in which sliding a lone occ urs. Validatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 15 publications
4
56
0
Order By: Relevance
“…We have used the Herron and Langway density-depth model in the diffusion model after comparing 5 density depth models. We found that the model of Arnaud et al (1998), Pimienta (Barnola et al, 1992 and Herron and Langway, (1980) pro-Fig. 12.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…We have used the Herron and Langway density-depth model in the diffusion model after comparing 5 density depth models. We found that the model of Arnaud et al (1998), Pimienta (Barnola et al, 1992 and Herron and Langway, (1980) pro-Fig. 12.…”
Section: Discussionmentioning
confidence: 68%
“…7 represent the ten firn sites used in this study. Here, the accumulation ranges from 0 to 1.2 m.w.eq.a −1 and temperature from 210 to 260 K. The figure indicates that the rather uncommon combination of low temperature and high accumulation will generally result in a deeper PCOD, which is consisted with other density depth models (Arnaud et al, 1998;Barnola et al, 1991;Kameda et al, 1994;Craven and Allison, 1998;and Spencer et al, 2001). This uncommon combination can explain the relatively deep PCOD at the South Pole (119 m) compared to Site M and Dome C (98.6 m).…”
Section: Results For Densitymentioning
confidence: 84%
See 1 more Smart Citation
“…[20] Figure 6 shows vertical and horizontal cross sections of five firn samples selected from a total of 23 samples, obtained using X-ray absorption microtomography. White and black areas indicate ice and pore space, respectively, and while grain boundaries are not observable with this method, they should exist at the site of bonding [e.g., Alley, 1987a;Arnaud et al, 1998]. The data provide the 3-D structure of firn and the progress of pore spaces toward bubble formation.…”
Section: Geometrical Structure Of Firnmentioning
confidence: 94%
“…In this case, diffusional water vapor transport in the pore space is solely driven by Kelvin effects. Conditions for long-term isothermal metamorphism occur in nature only in the center of the polar ice shields [Arnaud et al, 1998].…”
Section: Introductionmentioning
confidence: 99%